2019
DOI: 10.1016/j.jaad.2018.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Late growth of infantile hemangiomas in children >3 years of age: A retrospective study

Abstract: Background: The proliferative phase of infantile hemangiomas (IHs) is usually complete by 9 months of life. Late growth beyond age 3 years is rarely reported.Objective: To describe the demographic and clinic characteristics of a cohort of patients with late growth of IH, defined as growth in a patient [3 years of age.Methods: A multicenter, retrospective cohort study.Results: In total, 59 patients, 85% of which were female, met the inclusion criteria. The mean first episode of late growth was 4.3 (range 3-8.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Most of these lategrowth hemangiomas were classified as deep or mixed type hemangiomas (6). Growth after 36 months of age is rarely reported and more common in segmental hemangiomas of the head and neck and those involving deep and/or subcutaneous structures (7). Involution usually starts around 12-18 months of age, and can last for several years.…”
Section: Infantile Hemangiomamentioning
confidence: 99%
“…Most of these lategrowth hemangiomas were classified as deep or mixed type hemangiomas (6). Growth after 36 months of age is rarely reported and more common in segmental hemangiomas of the head and neck and those involving deep and/or subcutaneous structures (7). Involution usually starts around 12-18 months of age, and can last for several years.…”
Section: Infantile Hemangiomamentioning
confidence: 99%
“…Since the advent of propranolol, a number of reports have documented the incidence and risk factors associated with rebound growth 2,3 . A study of patients with late IH growth found associated factors to be larger IH size, segmental patterning, PHACE syndrome, presence of a deep component, and head and neck location 4 . In that cohort, ulceration was described in a subset of patients at initial presentation, but not as a complication of late or rebound growth.…”
Section: Discussionmentioning
confidence: 97%
“…The estimated risk of this complication is 25% in patients treated with propranolol 2,3 . IH growth after 3 years of age (late growth) is an uncommonly reported complication 4 . We present a series of three patients with segmental facial IH who experienced late growth and recurrent ulceration of the lower lip, requiring multimodal therapy and unusually prolonged treatment with systemic beta‐blockers.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lesions are associated with visceral involvement (especially liver and gastro intestinal tract). 3 , 9 , 13 , 14 , 15 Segmental and facial IH show a high risk of unaesthetic sequelae, complications, and recurrence. 9 , 11 , 13 However, there are yet no specific guidelines for the treatment of IH located on this topography, and that have a higher risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 9 , 13 , 14 , 15 Segmental and facial IH show a high risk of unaesthetic sequelae, complications, and recurrence. 9 , 11 , 13 However, there are yet no specific guidelines for the treatment of IH located on this topography, and that have a higher risk of recurrence. It seems obvious to think that for IH at high risk for complications, treatment with propranolol should be prolonged.…”
Section: Discussionmentioning
confidence: 99%